Nghiên cứu sử dụng than hoạt tính dạng sợi từ xơ đay để hấp phụ phenol và p-nitrophenol trong nước - Hòa, Phan Ngọc; Hồng, Nguyễn Thanh; Phong, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
The adsorption of phenol and p-nitrophenol has been performed by fibrous activated carbon from jute fiber. The adsorption is carried out in batch and in dynamic reactors. The results shown that adsorption capacities of phenol and p-nitrophenol on fibrous activated carbon were more than those of on the granular activated carbon. The breakthrough curves obtained with fibrous activated carbon for various bed thicknesses and flow rates were investigated. The adsorption capacity and adsorption zone of the columns were calculated. The best conditions for adsorption of phenol and p-nitro phenol on fibrous activated carbon (pH, initial concentrate, water flow rate) were determined.